Human Resource Management Strategy in La Fresa Kintamani Strawberry Cultivation Business, Bangli Rency, Bali Province - Pasaribu, Mika Damayanti; Widhiantini; I Dewa Ayu Sri Yudhari (Journal of Sustainable Development Science, 2024)
This research examines human resource (HR) management strategies in the La Fresa strawberry cultivation business in Kintamani, Bangli Regency. The aim of this research is to determine internal factors (strengths and weaknesses) and external factors (opportunities and threats), design alternative strategies and design superior strategies in developing human resources at La Fresa Kintamani Bangli. The variables used in this research are the company's internal and external variables. The data collection method used was in-depth interviews using questionnaires with ten key informants. The analysis methods used are the I-E matrix, SWOT analysis and QSPM matrix. The research results show from the I-E matrix that La Fresa Kintamani Bangli is in cell V, which means the company is in a stable condition with opportunities for growth. With the right strategy, La Fresa can take advantage of internal strengths and external opportunities to overcome existing weaknesses and threats, as well as increase the competitiveness and sustainability of the strawberry cultivation business in Kintamani, Bangli, Bali.